2008
DOI: 10.1016/j.ejcts.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation for surgical treatment of chronic atrial fibrillation combined with mitral valve surgery: a clinical observation

Abstract: Although in this study the efficacy rate of cryoablative surgery was not the same as classical Cox-Maze III, it seems that this procedure is safe, simple, cost-effective and at the same time does not increase the operative time significantly. Using cryoablation may enhance the cure rate of chronic AF during mitral valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
0
26
0
4
Order By: Relevance
“…However, in patients with small left atria (≤ 5cm) and lone paroxysmal AF, our center and others have had good results with pulmonary vein isolation, and this is a reasonable procedure that can be performed off CPB. In patients undergoing valve surgery, we have preferred a full CMP lesion set since the results of pulmonary vein isolation in these patients have generally been poor29, 33–36. Moreover, surgically converting AF into sinus rhythm has been associated with better early and late survival and less thromboembolic events during follow-up for patients with mitral valve disease3740.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with small left atria (≤ 5cm) and lone paroxysmal AF, our center and others have had good results with pulmonary vein isolation, and this is a reasonable procedure that can be performed off CPB. In patients undergoing valve surgery, we have preferred a full CMP lesion set since the results of pulmonary vein isolation in these patients have generally been poor29, 33–36. Moreover, surgically converting AF into sinus rhythm has been associated with better early and late survival and less thromboembolic events during follow-up for patients with mitral valve disease3740.…”
Section: Discussionmentioning
confidence: 99%
“…All nine papers were either small randomised controlled trials or retrospective studies with small sample sizes (57-521) and varied follow-up regimens. Six of nine studies [2,[4][5][6][7][8] suggested that cryoablation is most successful in patients suffering from paroxysmal rather than permanent AF. A lack of 24-hour monitoring in seven of nine studies [2-6, 9, 10] prevents effective elucidation of the rate of paroxysmal AF following cryoablation.…”
Section: Clinical Bottom Linementioning
confidence: 98%
“…Ghavidel et al [5] examined the use of cryoablation in either generating a Cox-Maze III pattern or in pulmonary vein isolation (PVI). They showed that there was no significant difference between the patterns in return to SR during 12-month follow-up.…”
Section: Search Outcomementioning
confidence: 99%
“…Ghavidel et al [22] used nitrous-based cryothermia energy on a group (n ¼ 90) who underwent surgical ablation (n ¼ 65 pulmonary vein isolation; n ¼ 25 biatrial Cox Maze) at the same time as their mitral valve surgery. They found that 65.5% of the patients were in SR at 12 months.…”
Section: Valvular Heart Diseasementioning
confidence: 99%